Power subgroups of Hecke groups H(n) - Nıhal Yilmaz; İ. Nacı Cangül (International Journal of Mathematics and Mathematical Sciences)
Results in discrete group theory are applied to some Hecke groups to determine the group theoretical structure of power subgroups.